MANAGEMENT ACCOUNTING SYSTEM IN STATE MEDICAL INSTITUTIONS AND ITS ORGANIZATIONAL ASPECTS (E Conference Zone, 2022)
This article describes the stages of creating a management accounting system in state medical institutions and ensuring its operation. the structure of the management account organization standard in state medical institutions is shown.